2015
DOI: 10.1037/a0038191
|View full text |Cite
|
Sign up to set email alerts
|

Why psychology? An investigation of the training in psychological literacy in nursing, medicine, social work, counselling psychology, and clinical psychology.

Abstract: Psychology is the science of human behavior. Thus, service providers in the area of mental health should have a foundational knowledge of psychological science; but do they? To investigate this question university calendars and websites were systematically reviewed to ascertain how many psychology courses and related training is required by entry level degrees for nursing, social work, medicine, counselling psychology, and clinical psychology. Results clearly show that clinical psychology graduates take more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 61 publications
0
36
0
Order By: Relevance
“…As a discipline and a profession, we need to answer the question: What makes psychology unique? 12 What unique knowledge and skills distinguishes our students from other graduates? 21 One problem is that psychology overlaps with many other disciplines and professions.…”
Section: Definitional and Conceptual Issuesmentioning
confidence: 99%
See 2 more Smart Citations
“…As a discipline and a profession, we need to answer the question: What makes psychology unique? 12 What unique knowledge and skills distinguishes our students from other graduates? 21 One problem is that psychology overlaps with many other disciplines and professions.…”
Section: Definitional and Conceptual Issuesmentioning
confidence: 99%
“…There are also numerous examples where a lack of psychological literacy is problematic. There are concerns that some professionals who provide mental health services lack sufficient psychological literacy, including family doctors, 11 13 nurses, 12 , 14 and social workers. 12 , 15 Doctors also lack knowledge regarding behavioral medicine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences between disciplines in terms of what students are taught about psychological literacy have been identified. Murdoch et al (2014) argue that there are three characteristics that set graduates of psychology apart from other health professionals. These are (1) knowledge and use of the scientific method of enquiry, (2) psychological literacy, and (3) the combined skills and knowledge of case formulation and diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…These are (1) knowledge and use of the scientific method of enquiry, (2) psychological literacy, and (3) the combined skills and knowledge of case formulation and diagnosis. Murdoch et al (2014) reviewed the amount and type of mental health training provided to students of psychology, nursing, social work, and medicine across universities in Canada. The data showed that psychology students received more instruction in psychological literacy in comparison to nursing, social work, and medical students, with the latter disciplines receiving approximately the same amount of instruction in psychological literacy as each other.…”
Section: Introductionmentioning
confidence: 99%